Analysis Of Drug Procurement Procedures At RSIA Muhaya Pangkalpinang Pharmaceutical Installation In 2023 - Muliana, Hilda; Wahab, Sabda; Azzahra, Nia (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2023)
Drug shortages in every healthcare unit are complex problems that require effective and efficient drug management. It is important to ensure the availability of drugs according to the right type and amount, preventing drug shortages and excesses. The purpose of this study is to analyze drug procurement procedures at RSIA Muhaya Pangkalpinang Pharmaceutical Installation in 2023. This research method is qualitative research with a descriptive analytical approach. Primary data collection was carried out by in-depth interview method with informants selected based on purposive sampling techniques. The information in this study consists of key informants and key informants. The results showed that in the drug procurement stage, there are frequent delays in receiving drugs from providers, drug vacancies occur in the e-catalogue system, and there are still frequent errors in the e-purchasing system. Thus, it has an impact on the availability of drugs at RSIA Muhaya Pangkalpinang.